Tool wear evaluation of self-propelled rotary tool and conventional round tool during turning Inconel 718 (Fracture and Structural Integrity, 2024)
Enhancing the machinability of difficult-to-cut materials is imperative, and a non-conventional rotary tool has shown high potential when machining these materials. This work comparatively evaluates the tool wear of conventional round tools (CRTs) and self-propelled rotary tools (SPRTs) when turning Inconel 718. Tool wear progression over time was measured and analyzed, simulated for various cutting conditions by creating mathematical and ANN models. This study found a 67% increase in tool life for SPRTs over CRTs, especially at a higher cutting speed of 65 m/min, due to improved heat transmission and steady wear distribution. However, at lower cutting conditions, the tool life gain was 15–18%, indicating that SPRTs could be reliably used at higher cutting conditions to achieve a machining economy. SPRTs exhibited better chip control and reduced built-up edge formation than CRTs. The cutting speed had the largest impact on tool flank wear, with machining time, feed, and depth of cut following closely behind. However, this effect was more prominent for CRTs. The 0.2 mm tool wear criterion was found to be more feasible since tool failure was caused by cutting tool chipping at this threshold instead of progressive growth of flank wear during Inconel 718 turning.
Keywords: Self-propelled rotary tools; Inconel 718; Adhesion; Tool wear; Modeling; Neural networks